NEW APPROACHES TO THE FORMATION OF LEGAL COMPETENCE IN ENGINEERING PEDAGOGY - S. V. Barabanova; R. I. Zinurova (Высшее образование в России)
The paper has been prepared on the basis of its authors' great experience in working in various areas at a technical university. It represents the result of long-term research and reflections on improving the legal support for engineering activities through developing the new forms of interaction between legal experts and engineers or between teaching staff and the management of engineering universities. The authors estimate the conventional approaches to organizing the teaching of future engineers legal disciplines as non-complying with the requirements of the modern engineering activities, and propose both to revise the contents of the existing courses and modify the organizational set-up of universities. Particularly, they propose to depart from traditional dividing into socio-humanistic and technical chairs and create an interdisciplinary department. Teaching legal disciplines at an engineering university is, in our opinion, necessary and actual. However, they should be taught focusing on developing legal literacy in students as future experts in engineering. This would require retraining the teachers of law, their active interaction with the representatives of engineering sciences, and conducting relevant scientific and applied research. Training of humanities majors studying at engineering universities should be transformed in a similar way: They have to acquire the basics ofengineering knowledge to increase their competitiveness on the labour market.